2015
DOI: 10.1002/chem.201500177
|View full text |Cite
|
Sign up to set email alerts
|

Cracking Cavitands: Metal‐Directed Scission of Phosphinyl‐Substituted Resorcinarenes

Abstract: Resorcinarene-derived tetramethylene cavitands bearing a diphenylphosphino group grafted to their wider rim undergo facile, directed C-O bond breaking upon reaction with transition-metal ions in the presence of nucleophiles. One possible reaction mechanism involves formation of a P,O-chelate complex, which weakens the adjacent O-CH2 bond, leading to the formation of an oxacarbenium intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…[7,9] We have previously shown that the treatment of 1 with the neutral complex [RuCl 2 (p-cymene)] 2 leads quantitatively to a single form of the chelate complex [RuCl(p-cymene)(P,O)] (3). [2] By extending this work to an investigation of the reaction of 1 with the bromido complex [RuBr 2 (p-cymene)] 2 under conditions similar to those applied for the preparation of 3, we have now found that two isomeric products result and can be distinguished readily by their 31 P NMR chemical shifts. Chromatographic separation gave the bromido complex 4, the crystalstructure determination of which (see below) showed it to be the analogue of 3, in 38 % yield and a minor product (5, 15 % yield, Scheme 3) with very similar spectroscopic properties and composition.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…[7,9] We have previously shown that the treatment of 1 with the neutral complex [RuCl 2 (p-cymene)] 2 leads quantitatively to a single form of the chelate complex [RuCl(p-cymene)(P,O)] (3). [2] By extending this work to an investigation of the reaction of 1 with the bromido complex [RuBr 2 (p-cymene)] 2 under conditions similar to those applied for the preparation of 3, we have now found that two isomeric products result and can be distinguished readily by their 31 P NMR chemical shifts. Chromatographic separation gave the bromido complex 4, the crystalstructure determination of which (see below) showed it to be the analogue of 3, in 38 % yield and a minor product (5, 15 % yield, Scheme 3) with very similar spectroscopic properties and composition.…”
Section: Resultsmentioning
confidence: 81%
“…These results define a rather rare system in which the solubility difference between the "racemic compound" and "racemic conglomerate" crystal forms of a chiral molecule is so slight that cocrystallisation is possible; [11] furthermore, this occurs through the formation of different solvates. 2 ], in which the two ligand units can adopt a rather remote disposition, may be indicative of the relative facility with which an intermediate Ni(P,O) species could accept a second cavitand ligand. A significant feature of the cavitand cleavage reaction is that it results in the conversion of the molecule from an achiral to a chiral form.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations